Test-retest reliability and concurrent validity of the unilateral seated shot-put test in patients with subacromial pain syndrome - Kararti, C.; Kodak, M. I.; Özyurt, F.; Basat, H. Ç.; Özsoy, I.; Özsoy, G.; Ilgar, M. Y. (Research in Sports Medicine, 2025)
The aim of this cross-sectional study was to assess the test-retest reliability and concurrent validity of the Unilateral Seated Shot-Put Test (USSPT) in patients with subacromial pain syndrome (SAPS). Twenty three patients were included in the study. The participants were assessed using the USSPT for functional power; Visual analog scale (VAS) for pain at activity; Disabilities of the Arm, Shoulder, and Hand Questionnaire (DASH) and Shoulder Pain and Disability Index (SPADI) for disability, hand-held dynamometer for shoulder flexion and shoulder abduction muscle strength, and grip strength. Test-retest reliability of the USSPT was found excellent with an intraclass correlation coefficient (ICC2,1) score of 0.976, a standard error of measurement (SEM) of 12.47, and a minimum detectable change (MDC95) score of 34.54. There was high to excellent correlations between the USSPT and the SPADI (r = -0.756, p = <0.001), shoulder flexion muscle strength (r = 0.834, p = <0.001), and shoulder abduction muscle strength (r = 0.711, p = <0.001). SPADI score and shoulder flexion muscle strength were the most important factors influencing USSPT performance, accounting for 73.3% of the variance. The USSPT is a reliable and valid test for assessing upper extremity functional power.